Integrated metabolomic and transcriptomic analysis of anthocyanin metabolism in wheat pericarp - Jiao Wang; Lei Sun; Bo Jiao; Pu Zhao; Tianyun Xu; Sa Gu; Chenmin Huo; Jianzhou Pang; Shuo Zhou (BMC Genomic Data)
Abstract Background Wheat seeds display different colors due to the types and contents of anthocyanins, which is closely related to anthocyanin metabolism. In this study, a transcriptomic and metabolomic analysis between white and purple color wheat pericarp aimed to explore some key genes and metabolites involved in anthocyanin metabolism. Results Two wheat cultivars, a white seed cultivar Shiluan02-1 and purple seed cultivar Hengzi151 were used to identify the variations in differentially expressed genes (DEGs) and differentially accumulated flavonoids (DAFs). Based on metabolomic data, 314 metabolites and 191 DAFs were identified. Chalcone, flavonol, pro-anthocyanidin and anthocyanidin were the most differentially accumulated flavonoid compounds in Hengzi151. 2610 up-regulated and 2668 down-regulated DEGs were identified according to transcriptomic data. The results showed that some structural genes in anthocyanin synthesis pathway were prominently activated in Hengzi151, such as PAL, CAD, CHS and so on. Transcription factors (TFs) of MYB, bHLH, WD40 and some other TFs probably involved in regulating anthocyanin biosynthesis were identified. Some genes from hormone synthetic and signaling pathways that may participate in regulating anthocyanin biosynthesis also have been identified. Conclusions Our results provide valuable information on the candidate genes and metabolites involved in the anthocyanin metabolism in wheat pericarp.